Encephalitis with mGluR5 antibodies: Symptoms and antibody effects. (29th May 2018) - Spatola, Marianna; Sabater, Lidia; Planagumà, Jesús; Martínez-Hernandez, Eugenia; Armangué, Thaís; Prüss, Harald; Iizuka, Takahiro; Caparó Oblitas, Ruben L.; Antoine, Jean-Christophe; Li, Richard; Heaney, Nicholas; Tubridy, Niall; et al.
Abstract : Objective: To report the clinical features of 11 patients with metabotropic glutamate receptor 5 (mGluR5) antibody–associated encephalitis, immunoglobulin G (IgG) subclass, and effects of the antibodies on neuronal mGluR5 clusters. Methods: Clinical information was retrospectively obtained from referring physicians. Antibodies to mGluR5 and IgG subclasses were determined with brain immunohistochemistry and cell-based assays. The effects of the antibodies were examined on rat hippocampal neurons with reported techniques. Results: From January 2005 to May 2017, 11 patients (median age 29 years, range 6–75 years, 5 female) were identified. The main clinical features were psychiatric (10), cognitive (10), movement disorders (7), sleep dysfunction (7), and seizures (6). Median modified Rankin Scale score at the peak of the disease was 4; 4 patients required intensive care. Five patients had Hodgkin lymphoma, and 1 had small cell lung cancer. CSF showed pleocytosis (median white blood cell count 22 mm 3 ) in all patients; brain MRI was abnormal in 5, involving limbic (1) or extralimbic (4) regions. Treatments included immunotherapy and/or oncologic therapy; at the last follow-up (median 48 months), 6 patients had complete and 5 had partial recovery. Neurologic relapse occurred in 2 patients. Antibodies were IgG1 alone (4 of 9) or in combination with IgG2 (1 of 9), IgG3 (3 of 9), or both (1). Patients' IgG caused a significant and specific decrease of cell-surface synaptic and extrasynaptic mGluR5 without altering the levels of postsynaptic density protein 95. Conclusions: Anti-mGluR5 encephalitis associates with a complex neuropsychiatric syndrome, not restricted to limbic encephalitis, and can occur without tumor. Patients respond to treatment, but relapses can occur. The antibodies have pathogenic effects altering the levels of cell-surface mGluR5.